Aberrant methylation of Serpine1 mediates lung injury in neonatal mice prenatally exposed to intrauterine inflammation - Dongting Yao; Jiuru Zhao; Qianqian Zhang; Tao Wang; Meng Ni; Sudong Qi; Qianwen Shen; Wei Li; Baihe Li; Xiya Ding; Zhiwei Liu (figshare, 2022)
Abstract Background Intrauterine inflammation (IUI) alters epigenetic modifications in offspring, leading to lung injury. However, the epigenetic mechanism underlying IUI-induced lung injury remains uncertain. In the present study, we aim to investigate the effect of IUI on lung development, and to identify the key molecule involved in this process and its epigenetic regulatory mechanism. Results Serpine1 was upregulated in the lung tissue of neonatal mice with IUI. Intranasal delivery of Serpine1 siRNA markedly reversed IUI-induced lung injury. Serpine1 overexpression substantially promoted cell senescence of both human and murine lung epithelial cells, reflected by decreased cell proliferation and increased senescence-associated β-galactosidase activity, G0/G1 cell fraction, senescence marker, and oxidative and DNA damage marker expression. IUI decreased the methylation level of the Serpine1 promoter, and methylation of the promoter led to transcriptional repression of Serpine1. Furthermore, IUI promoted the expression of Tet1 potentially through TNF-α, while Tet1 facilitated the demethylation of Serpine1 promoter. DNA pull-down and ChIP assays revealed that the Serpine1 promoter was regulated by Rela and Hdac2. DNA demethylation increased the recruitment of Rela to the Serpine1 promoter and induced the release of Hdac2. Conclusion Increased Serpine1 expression mediated by DNA demethylation causes lung injury in neonatal mice with IUI. Therefore, therapeutic interventions targeting Serpine1 may effectively prevent IUI-induced lung injury.
Keywords: Genetics